Composite solid electrolyte membrane, preparation method and preparation process of solid lithium metal battery

By combining the deep eutectic solution with the oxide electrolyte LAGP and polytetrafluoroethylene PTFE, a composite solid electrolyte membrane is prepared, which solves the problems of poor contact between the oxide electrolyte and the electrode and large interface ion transmission resistance, and achieves a solid lithium metal battery with high safety and long cycle performance, which is suitable for large-scale production.

CN120545446APending Publication Date: 2025-08-26JIANGSU UNIQUE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510679210.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing oxide electrolytes have poor contact with the electrode, large interface ion transport resistance, and it is difficult to directly form oxide ceramics, which limits the large-scale production of solid-state lithium metal batteries.

Method used

The composite solid electrolyte film is prepared by combining deep eutectic solution with oxide electrolyte LAGP and polytetrafluoroethylene PTFE through high temperature stirring, ball milling and roll pressing. Combined with the positive and negative electrode assembly process of lithium metal batteries, a solid lithium metal battery with a three-layer structure of 5-5-6 is formed.

Benefits of technology

It improves the transmission rate of lithium ions in ceramic networks, enhances the ionic conductivity of the electrolyte membrane, and achieves a solid-state lithium metal battery with high safety and long cycle performance, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005418720170000101
    Figure BDA0005418720170000101
  • Figure BDA0005418720170000111
    Figure BDA0005418720170000111
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte membrane, a preparation method and a preparation process of a solid lithium metal battery. The preparation method comprises the following steps: adding a nitrile source and a lithium source into a high-temperature stirrer according to a molar ratio of (6-8): (2-4), heating at 50 DEG C, and stirring for 2 hours to obtain a deep eutectic solution; the preparation method comprises the following steps: putting an oxide electrolyte LAGP and polytetrafluoroethylene PTFE in a mass ratio of 1: (0.01-0.06) into a zirconium oxide ball milling tank, and grinding for 0.5-3 hours at a rotating speed of 200-400 revolutions per minute to obtain an electrolyte ground material; the deep eutectic solution is added into a zirconium oxide ball milling tank and mixed with an electrolyte grinding substance, the mass ratio of the deep eutectic solution to the electrolyte grinding substance is (25-50): (50-75), grinding is conducted for 1-5 h at the rotating speed of 200-400 r / min, and a mixture is obtained; and putting the mixture into multi-roller rolling equipment, heating a roller to 110 DEG C, rolling and thinning the mixture to obtain a membrane with uniform thickness, and cutting the membrane into the composite solid electrolyte membrane. The concentration of free Li < + > is improved, and the ionic conductivity of the composite solid electrolyte membrane is improved. According to the method, the polymer and the oxide ceramic are combined, the film is directly prepared, the battery can be produced on a large scale, and the compatibility with the current production line is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of solid-state lithium metal battery production, and in particular relates to a composite solid-state electrolyte membrane, a preparation method and a solid-state lithium metal battery preparation process. Background technology:

[0002] Solid-state lithium metal batteries are considered the most promising energy storage technology in the future due to their high theoretical energy density and reliable safety. To realize the application of high-performance solid-state lithium metal batteries, it is crucial to develop solid electrolytes with high ionic conductivity and long-lasting electrochemical stability.

[0003] Oxide electrolytes have a very high ionic conductivity (10 -3 S / cm), long-lasting electrochemical stability, and excellent mechanical strength. However, oxides have poor contact with electrodes and high interfacial ion transport resistance. Furthermore, due to the inherent brittleness of oxides, oxide ceramics are difficult to directly form into membranes for use in batteries. The preparation of oxide solid ceramics requires high-temperature sintering, which limits large-scale production.

[0004] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0005] The purpose of the present invention is to provide a solid electrolyte that makes improvements in both the electrode-electrolyte interface and ionic conductivity, thereby achieving high safety and long cycle performance of solid-state lithium metal batteries, thereby overcoming the above-mentioned defects in the prior art.

[0006] To achieve the above-mentioned object, the present invention provides a composite solid electrolyte membrane, the mass components of which are: 25-50 parts of a deep eutectic solution and 50-75 parts of an electrolyte; wherein the deep eutectic solution includes a nitrile source and a lithium source, and the nitrile source and the lithium source are configured in a molar ratio of 6-8:2-4; wherein the electrolyte includes an oxide electrolyte LAGP and polytetrafluoroethylene PTFE, and the mass ratio of the oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.01-0.06.

[0007] Preferably, in the technical solution, the nitrile source is selected from one of succinonitrile, glutaronitrile, 1,2,3-propanetricarboxylic acid nitrile, ethylsuccinonitrile, 2-methyleneglutaronitrile, methylglutaronitrile, phenylsuccinic acid nitrile, and 2,2,3,3-tetrafluorosuccinonitrile.

[0008] Preferably, in the technical solution, the lithium source is at least one of LiPF6, LiFSi, LiTFSi, LiDFP, LiBOB, LiDFOB, LiDFOP, and LiOTFP.

[0009] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) adding a nitrile source and a lithium source in a molar ratio of 6-8:2-4 into a high-temperature stirrer, heating at 50° C., and stirring for 2 h to obtain a deep eutectic solution;

[0010] (2) placing the oxide electrolyte LAGP and polytetrafluoroethylene (PTFE) in a zirconia ball mill at a mass ratio of 1:0.01-0.06, and grinding at a speed of 200-400 rpm for 0.5-3 h to obtain an electrolyte grind;

[0011] (3) adding the deep eutectic solution obtained in step (1) into a zirconia ball mill, mixing with the electrolyte grind, wherein the mass ratio of the deep eutectic solution to the electrolyte grind is 25-50:50-75, and grinding at a speed of 200-400 rpm for 1-5 hours to obtain a mixture;

[0012] (4) The mixture is placed in a multi-roller pressing device, the rollers are heated to 110°C, and the mixture is rolled and thinned to obtain a membrane with uniform thickness. The membrane is cut into a composite solid electrolyte membrane that meets the requirements.

[0013] A process for preparing a solid-state lithium metal battery comprises the following steps: (1) preparing a composite solid electrolyte membrane by using a composite solid electrolyte membrane preparation method;

[0014] (2) Add 95-98 parts by mass of lithium nickel cobalt manganate ternary material LiNi9CoMnO2, 2-3 parts of conductive agent, 0.5-1.5 parts of binder, and 0.2-0.8 parts of carbon nanotubes into a blender, stir at a speed of 1000-3000 r / s for 4-6 hours, and mix the components evenly to obtain a positive electrode slurry with a viscosity of 5000-20000 mPa·s;

[0015] (3) coating the positive electrode slurry obtained in step (2) on an aluminum foil for current collector, drying at 85° C. and cold pressing to obtain a positive electrode blank; trimming, cutting, and slitting the positive electrode blank, and drying under vacuum at 85° C. for 8 h to obtain a lithium metal battery positive electrode sheet;

[0016] (4) using a copper foil coated with lithium on both sides as a negative electrode blank, trimming, cutting, and slitting the negative electrode blank to obtain a lithium metal battery negative electrode sheet;

[0017] (5) stacking 6 lithium metal battery negative electrode sheets in sequence, stacking 5 composite solid electrolyte membranes in sequence on the top layer of lithium metal battery negative electrode sheets, and stacking 5 lithium metal battery positive electrode sheets in sequence on the top layer of composite solid electrolyte membrane to obtain solid-state lithium metal battery blank sheets; the solid-state lithium metal battery blank sheets form a 5-5-6 three-layer structure from top to bottom;

[0018] (6) placing the solid-state lithium metal battery blank into an isostatic pressing furnace, and performing segmented pressurization from low pressure to medium and high pressure, wherein the low pressure range is 0.5-3 MPa, and the medium and high pressure range is 3-10 MPa. During the segmented pressurization process, the pressurization time for each segment is 8-12 minutes, and the total pressurization time is 12 hours, thereby obtaining a battery cell;

[0019] (7) Place the battery cell in an ultrasonic welding machine and weld the current collectors of the positive and negative electrodes of the battery cell to the corresponding positive and negative electrode tabs at a frequency of 20kHz-40kHz; the positive electrode tab is aluminum foil and the negative electrode tab is copper foil;

[0020] (8) The welded battery cell is packaged using a soft-pack battery packaging process to obtain a solid-state lithium metal battery.

[0021] Preferably, in the technical solution, the conductive agent in step (2) is selected from one of conductive carbon black super-p, carbon nanotubes CNT, and carbon nanofibers VGCF.

[0022] Preferably, in the technical solution, the adhesive in step (2) is polyvinylidene fluoride (PVDF).

[0023] Preferably, in the technical solution, the thickness of the copper foil in step (4) is 8 μm, and the thickness of lithium on both sides of the copper foil is 50 μm.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The oxide electrolyte LAGP particles are condensed together by polytetrafluoroethylene (PTFE) fibers and surrounded by a deep eutectic solution mixture, which improves the interfacial contact between the LAGP particles and enables lithium ions to transfer rapidly in the interconnected ceramic network. The deep eutectic solution fills the voids in the polytetrafluoroethylene (PTFE) fibers, acting as a highway for lithium ion transport and facilitating lithium ion migration. The terminal nitrile group interacts with the anion of the lithium salt, anchoring the anion and preventing its migration, thereby increasing the free Li + The concentration of ions increases the ionic conductivity of the composite solid electrolyte membrane. This method combines polymers and oxide ceramics to directly form membranes, which can be mass-produced for batteries and has high compatibility with current production lines. Specific implementation method:

[0026] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0027] Unless expressly stated otherwise, throughout the specification and claims, the term "comprise" or variations such as "include" or "comprising", etc., will be understood to include the stated elements or components but not to exclude other elements or other components.

[0028] Example 1

[0029] A composite solid electrolyte membrane, the mass components of which are: 40 parts of deep eutectic solution and 60 parts of electrolyte; wherein the deep eutectic solution comprises succinonitrile and LiTFSi, and the succinonitrile and LiTFSi are configured in a molar ratio of 8:2; wherein the electrolyte comprises an oxide electrolyte Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), polytetrafluoroethylene PTFE, the mass ratio of oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.04.

[0030] A preparation process for a solid-state lithium metal battery comprises the following steps: (1) adding succinonitrile and LiTFSi in a molar ratio of 8:2 to a high-temperature mixer, heating at 50°C and stirring for 2 hours to obtain a deep eutectic solution; placing an oxide electrolyte LAGP and polytetrafluoroethylene (PTFE) in a mass ratio of 1:0.04 into a zirconia ball mill, grinding at a speed of 300 rpm for 1 hour to obtain an electrolyte grind; adding the deep eutectic solution into the zirconia ball mill, mixing with the electrolyte grind, wherein the mass ratio of the deep eutectic solution to the electrolyte grind is 40:60, grinding at a speed of 300 rpm for 2 hours to obtain a mixture; placing the mixture into a multi-roller rolling device, heating the rollers to 110°C, rolling and thinning the mixture to obtain a membrane with uniform thickness, and cutting the membrane into a composite solid electrolyte membrane that meets the requirements;

[0031] (2) 96.5 parts by mass of lithium nickel cobalt manganese oxide ternary material LiNi9CoMnO2, 2.5 parts by mass of conductive carbon black super-p, 1 part by mass of polyvinylidene fluoride PVDF, and 0.5 parts by mass of carbon nanotubes were added into a blender and stirred at a speed of 2000 r / s for 5 h to mix the components uniformly to obtain a positive electrode slurry with a viscosity of 15000 mPa·s;

[0032] (3) coating the positive electrode slurry obtained in step (2) on an aluminum foil for current collector, drying at 85° C. and cold pressing to obtain a positive electrode blank; trimming, cutting, and slitting the positive electrode blank, and drying under vacuum at 85° C. for 8 h to obtain a lithium metal battery positive electrode sheet;

[0033] (4) Using a copper foil coated with lithium on both sides as a negative electrode blank, the copper foil has a thickness of 8 μm, and the thickness of lithium on both sides of the copper foil is 50 μm. After trimming, cutting, and slitting the negative electrode blank, a lithium metal battery negative electrode sheet is obtained;

[0034] (5) stacking 6 lithium metal battery negative electrode sheets in sequence, stacking 5 composite solid electrolyte membranes in sequence on the top layer of lithium metal battery negative electrode sheets, and stacking 5 lithium metal battery positive electrode sheets in sequence on the top layer of composite solid electrolyte membrane to obtain solid-state lithium metal battery blank sheets; the solid-state lithium metal battery blank sheets form a 5-5-6 three-layer structure from top to bottom;

[0035] (6) placing the solid-state lithium metal battery blank into an isostatic pressing furnace, and performing segmented pressurization from low pressure to medium and high pressure, wherein the low pressure range is 0.5-3 MPa, and the medium and high pressure range is 3-10 MPa. During the segmented pressurization process, the pressurization time for each segment is 10 min, and the total pressurization time is 12 h, thereby obtaining a battery cell;

[0036] (7) Place the battery cell in an ultrasonic welding machine and weld the current collectors of the positive and negative electrodes of the battery cell to the corresponding positive and negative electrode tabs at a frequency of 30 kHz; the positive electrode tab is aluminum foil and the negative electrode tab is copper foil;

[0037] (8) The soft pack battery packaging process is adopted. The aluminum-plastic film is punched through a mold to form a pit to accommodate the battery cell. The welded battery cell is placed in the pit. The PP layer is sealed at the edge by hot pressing at 180-220℃, leaving a liquid injection port. The liquid is injected in a low dew point environment (≤-40℃) to avoid moisture residue. After formation, the gas is extracted, and the battery is heat-sealed for the second time and the excess edges are cut off to obtain a solid-state lithium metal battery with a capacity of 2Ah.

[0038] Example 2

[0039] A composite solid electrolyte membrane, the mass components of which are: 25 parts of deep eutectic solution and 75 parts of electrolyte; wherein the deep eutectic solution comprises glutaronitrile, LiTFSi, and LiDFOB, and the glutaronitrile, LiTFSi, and LiDFOB are configured in a molar ratio of 7:2:1; wherein the electrolyte comprises an oxide electrolyte Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), polytetrafluoroethylene PTFE, the mass ratio of oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.04.

[0040] A preparation process for a solid-state lithium metal battery comprises the following steps: (1) adding glutaronitrile, LiTFSi, and LiDFOB in a molar ratio of 7:2:1 to a high-temperature mixer, heating at 50°C, and stirring for 2 hours to obtain a deep eutectic solution; placing an oxide electrolyte LAGP and polytetrafluoroethylene (PTFE) in a mass ratio of 1:0.04 into a zirconia ball mill, grinding at a speed of 300 rpm for 1 hour to obtain an electrolyte grind; adding the deep eutectic solution into the zirconia ball mill, mixing it with the electrolyte grind, the mass ratio of the deep eutectic solution to the electrolyte grind being 25:75, grinding at a speed of 300 rpm for 3 hours to obtain a mixture; placing the mixture into a multi-roller rolling device, heating the rollers to 110°C, rolling and thinning the mixture to obtain a membrane with uniform thickness, and cutting the membrane into a composite solid electrolyte membrane that meets the requirements;

[0041] (2) 96.5 parts by mass of lithium nickel cobalt manganese oxide ternary material LiNi9CoMnO2, 2.5 parts by mass of conductive carbon black super-p, 1 part by mass of polyvinylidene fluoride PVDF, and 0.5 parts by mass of carbon nanotubes were added into a blender and stirred at a speed of 2000 r / s for 5 h to mix the components uniformly to obtain a positive electrode slurry with a viscosity of 15000 mPa·s;

[0042] (3) coating the positive electrode slurry obtained in step (2) on an aluminum foil for current collector, drying at 85° C. and cold pressing to obtain a positive electrode blank; trimming, cutting, and slitting the positive electrode blank, and drying under vacuum at 85° C. for 8 h to obtain a lithium metal battery positive electrode sheet;

[0043] (4) Using a copper foil coated with lithium on both sides as a negative electrode blank, the copper foil has a thickness of 8 μm, and the thickness of lithium on both sides of the copper foil is 50 μm. After trimming, cutting, and slitting the negative electrode blank, a lithium metal battery negative electrode sheet is obtained;

[0044] (5) stacking 6 lithium metal battery negative electrode sheets in sequence, stacking 5 composite solid electrolyte membranes in sequence on the top layer of lithium metal battery negative electrode sheets, and stacking 5 lithium metal battery positive electrode sheets in sequence on the top layer of composite solid electrolyte membrane to obtain solid-state lithium metal battery blank sheets; the solid-state lithium metal battery blank sheets form a 5-5-6 three-layer structure from top to bottom;

[0045] (6) placing the solid-state lithium metal battery blank into an isostatic pressing furnace, and performing segmented pressurization from low pressure to medium and high pressure, wherein the low pressure range is 0.5-3 MPa, and the medium and high pressure range is 3-10 MPa. During the segmented pressurization process, the pressurization time for each segment is 10 min, and the total pressurization time is 12 h, thereby obtaining a battery cell;

[0046] (7) Place the battery cell in an ultrasonic welding machine and weld the current collectors of the positive and negative electrodes of the battery cell to the corresponding positive and negative electrode tabs at a frequency of 30 kHz; the positive electrode tab is aluminum foil and the negative electrode tab is copper foil;

[0047] (8) The soft pack battery packaging process is adopted. The aluminum-plastic film is punched through a mold to form a pit to accommodate the battery cell. The welded battery cell is placed in the pit. The PP layer is sealed at the edge by hot pressing at 180-220℃, leaving a liquid injection port. The liquid is injected in a low dew point environment (≤-40℃) to avoid moisture residue. After formation, the gas is extracted, and the battery is heat-sealed for the second time and the excess edges are cut off to obtain a solid-state lithium metal battery with a capacity of 2Ah.

[0048] Example 3

[0049] A composite solid electrolyte membrane, the mass components of which are: 50 parts of deep eutectic solution and 50 parts of electrolyte; wherein the deep eutectic solution comprises succinonitrile and LiTFSi, and the succinonitrile and LiTFSi are configured in a molar ratio of 8:2; wherein the electrolyte comprises an oxide electrolyte Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), polytetrafluoroethylene PTFE, the mass ratio of oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.04.

[0050] A preparation process for a solid-state lithium metal battery comprises the following steps: (1) adding succinonitrile and LiTFSi in a molar ratio of 8:2 to a high-temperature mixer, heating at 50°C and stirring for 2 hours to obtain a deep eutectic solution; placing an oxide electrolyte LAGP and polytetrafluoroethylene (PTFE) in a mass ratio of 1:0.04 into a zirconia ball mill, grinding at a speed of 300 rpm for 1 hour to obtain an electrolyte grind; adding the deep eutectic solution into the zirconia ball mill, mixing with the electrolyte grind, the mass ratio of the deep eutectic solution to the electrolyte grind being 50:50, grinding at a speed of 300 rpm for 2 hours to obtain a mixture; placing the mixture into a multi-roller rolling device, heating the rollers to 110°C, rolling and thinning the mixture to obtain a membrane with uniform thickness, and cutting the membrane into a composite solid electrolyte membrane that meets the requirements;

[0051] (2) 96.5 parts by mass of lithium nickel cobalt manganese oxide ternary material LiNi9CoMnO2, 2.5 parts by mass of conductive carbon black super-p, 1 part by mass of polyvinylidene fluoride PVDF, and 0.5 parts by mass of carbon nanotubes were added into a blender and stirred at a speed of 2000 r / s for 5 h to mix the components uniformly to obtain a positive electrode slurry with a viscosity of 15000 mPa·s;

[0052] (3) coating the positive electrode slurry obtained in step (2) on an aluminum foil for current collector, drying at 85° C. and cold pressing to obtain a positive electrode blank; trimming, cutting, and slitting the positive electrode blank, and drying under vacuum at 85° C. for 8 h to obtain a lithium metal battery positive electrode sheet;

[0053] (4) Using a copper foil coated with lithium on both sides as a negative electrode blank, the copper foil has a thickness of 8 μm, and the thickness of lithium on both sides of the copper foil is 50 μm. After trimming, cutting, and slitting the negative electrode blank, a lithium metal battery negative electrode sheet is obtained;

[0054] (5) stacking 6 lithium metal battery negative electrode sheets in sequence, stacking 5 composite solid electrolyte membranes in sequence on the top layer of lithium metal battery negative electrode sheets, and stacking 5 lithium metal battery positive electrode sheets in sequence on the top layer of composite solid electrolyte membrane to obtain solid-state lithium metal battery blank sheets; the solid-state lithium metal battery blank sheets form a 5-5-6 three-layer structure from top to bottom;

[0055] (6) placing the solid-state lithium metal battery blank into an isostatic pressing furnace, and performing segmented pressurization from low pressure to medium and high pressure, wherein the low pressure range is 0.5-3 MPa, and the medium and high pressure range is 3-10 MPa. During the segmented pressurization process, the pressurization time for each segment is 10 min, and the total pressurization time is 12 h, thereby obtaining a battery cell;

[0056] (7) Place the battery cell in an ultrasonic welding machine and weld the current collectors of the positive and negative electrodes of the battery cell to the corresponding positive and negative electrode tabs at a frequency of 30 kHz; the positive electrode tab is aluminum foil and the negative electrode tab is copper foil;

[0057] (8) The soft pack battery packaging process is adopted. The aluminum-plastic film is punched through a mold to form a pit to accommodate the battery cell. The welded battery cell is placed in the pit. The PP layer is sealed at the edge by hot pressing at 180-220℃, leaving a liquid injection port. The liquid is injected in a low dew point environment (≤-40℃) to avoid moisture residue. After formation, the gas is extracted, and the battery is heat-sealed for the second time and the excess edges are cut off to obtain a solid-state lithium metal battery with a capacity of 2Ah.

[0058] Comparative Example 1

[0059] A solid electrolyte membrane, comprising: an oxide electrolyte Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), polytetrafluoroethylene PTFE, the mass ratio of oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.04.

[0060] A preparation process for a solid-state lithium metal battery comprises the following steps: using the above-mentioned solid electrolyte membrane to prepare a soft-pack battery with the same capacity as that of Example 1.

[0061] test

[0062] The composite solid electrolyte membranes of Examples 1-3 and the solid electrolyte membrane of Comparative Example 1 were subjected to Test A, and the soft-pack batteries of Examples 1-3 and Comparative Example 1 were subjected to Test B.

[0063] A: Ionic conductivity test

[0064] The solid electrolyte membrane was assembled into a blocked symmetrical cell with stainless steel blocking electrodes at both ends. The resistance was measured by AC impedance using an electrochemical workstation, and the ionic conductivity of the solid electrolyte was calculated using formula (1). The test frequency was 0.01 Hz to 1 MHz, the test perturbation voltage was 5 mV, and the test temperature was the actual temperature inside the glove box.

[0065] σ=L / (R*S) (1)

[0066] Where σ is the ionic conductivity of the solid electrolyte (S / cm); L is the thickness of the solid electrolyte (cm); R is the intrinsic resistance of the solid electrolyte (Ω); S is the cross-sectional area of ​​the solid electrolyte (cm 2 ).

[0067] B: Cycle test

[0068] Cycling tests were carried out in a 35°C constant temperature chamber using a LAND CT2001A test system at a charge and discharge rate of 0.2 / 1C. The charge and discharge cut-off voltages were 4.2V and 2.5V, respectively. The battery capacity retention rate was recorded after 100 cycles.

[0069] The results of Test A and Test B are shown in Table 1.

[0070] Table 1 Test results of Test A and Test B of Examples 1-3 and Comparative Example 1

[0071]

[0072]

[0073] Note: If the cycle test capacity retention rate of the soft-pack lithium metal battery is less than 80%, the battery test will be stopped.

[0074] As can be seen from Table 1, through Examples 1-3, it can be seen that the present invention effectively improves the battery capacity and capacity retention rate by combining a deep eutectic solution with an electrolyte, dry-forming a membrane, and assembling a solid-state lithium metal battery. The composite solid electrolyte membrane obtained by the method of each embodiment of the present invention has a high ionic conductivity, all greater than 0.3ms / cm, and the assembled solid-state lithium metal battery has excellent cycle performance.

[0075] The foregoing descriptions of specific exemplary embodiments of the present invention are for purposes of illustration and description. These descriptions are not intended to limit the invention to the precise forms disclosed, and it is apparent that many variations and modifications are possible in light of the foregoing teachings. The exemplary embodiments have been selected and described for the purpose of explaining the specific principles of the invention and their practical application, thereby enabling those skilled in the art to realize and utilize a variety of exemplary embodiments of the invention and various options and modifications. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A composite solid electrolyte membrane, characterized in that: The mass components are 25-50 parts of a deep eutectic solution and 50-75 parts of an electrolyte; the deep eutectic solution includes a nitrile source and a lithium source, and the nitrile source and the lithium source are configured in a molar ratio of 6-8:2-4; the electrolyte includes an oxide electrolyte LAGP and polytetrafluoroethylene PTFE, and the mass ratio of the oxide electrolyte LAGP and polytetrafluoroethylene PTFE is 1:0.01-0.

06.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The nitrile source is selected from one of succinonitrile, glutaronitrile, 1,2,3-propanetricarbonitrile, ethylsuccinonitrile, 2-methyleneglutaronitrile, methylglutaronitrile, phenylsuccinic acid nitrile and 2,2,3,3-tetrafluorosuccinonitrile.

3. The composite solid electrolyte membrane according to claim 2, characterized in that: The lithium source is at least one of LiPF6, LiFSi, LiTFSi, LiDFP, LiBOB, LiDFOB, LiDFOP, and LiOTFP.

4. A method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 3, comprising the steps of: (1) adding a nitrile source and a lithium source in a molar ratio of 6-8:2-4 to a high-temperature mixer, heating at 50°C, and stirring for 2 hours to obtain a deep eutectic solution; (2) placing the oxide electrolyte LAGP and polytetrafluoroethylene (PTFE) in a zirconia ball mill at a mass ratio of 1:0.01-0.06, and grinding at a speed of 200-400 rpm for 0.5-3 h to obtain an electrolyte grind; (3) adding the deep eutectic solution obtained in step (1) into a zirconia ball mill, mixing with the electrolyte grind, wherein the mass ratio of the deep eutectic solution to the electrolyte grind is 25-50:50-75, and grinding at a speed of 200-400 rpm for 1-5 hours to obtain a mixture; (4) The mixture is placed in a multi-roller pressing device, the rollers are heated to 110° C., and the mixture is rolled and thinned to obtain a membrane with uniform thickness, and the membrane is cut into a composite solid electrolyte membrane.

5. A process for preparing a solid-state lithium metal battery, comprising the steps of: (1) preparing a composite solid electrolyte membrane using the method for preparing a composite solid electrolyte membrane as claimed in claim 4; (2) Add 95-98 parts by mass of lithium nickel cobalt manganate ternary material LiNi9CoMnO2, 2-3 parts of conductive agent, 0.5-1.5 parts of adhesive, and 0.2-0.8 parts of carbon nanotubes into a blender, stir at a speed of 1000-3000 r / s for 4-6 hours, and mix the components evenly to obtain a positive electrode slurry with a viscosity of 5000-20000 mPa·s; (3) coating the positive electrode slurry obtained in step (2) on an aluminum foil for current collector, drying at 85° C. and cold pressing to obtain a positive electrode blank; trimming, cutting, and slitting the positive electrode blank, and drying under vacuum at 85° C. for 8 h to obtain a lithium metal battery positive electrode sheet; (4) using a copper foil coated with lithium on both sides as a negative electrode blank, trimming, cutting, and slitting the negative electrode blank to obtain a lithium metal battery negative electrode sheet; (5) stacking 6 lithium metal battery negative electrode sheets in sequence, stacking 5 composite solid electrolyte membranes in sequence on the top layer of lithium metal battery negative electrode sheets, and stacking 5 lithium metal battery positive electrode sheets in sequence on the top layer of composite solid electrolyte membrane to obtain solid-state lithium metal battery blank sheets; the solid-state lithium metal battery blank sheets form a 5-5-6 three-layer structure from top to bottom; (6) placing the solid-state lithium metal battery blank into an isostatic pressing furnace, and performing segmented pressurization from low pressure to medium and high pressure, wherein the low pressure range is 0.5-3 MPa, and the medium and high pressure range is 3-10 MPa. During the segmented pressurization process, the pressurization time for each segment is 8-12 minutes, and the total pressurization time is 12 hours, thereby obtaining a battery cell; (7) Place the battery cell in an ultrasonic welding machine and weld the current collectors of the positive and negative electrodes of the battery cell to the corresponding positive and negative electrode tabs at a frequency of 20kHz-40kHz; the positive electrode tab is aluminum foil and the negative electrode tab is copper foil; (8) The welded battery cell is packaged using a soft-pack battery packaging process to obtain a solid-state lithium metal battery.

6. The process for preparing a solid-state lithium metal battery according to claim 5, wherein: In step (2), the conductive agent is selected from one of conductive carbon black super-p, carbon nanotubes CNT, and carbon nanofibers VGCF.

7. The process for preparing a solid-state lithium metal battery according to claim 6, wherein: In step (2), the adhesive is polyvinylidene fluoride (PVDF).

8. The process for preparing a solid-state lithium metal battery according to claim 5, wherein: In step (4), the thickness of the copper foil is 8 μm, and the thickness of lithium on both sides of the copper foil is 50 μm.